Human Infection with MERS Coronavirus after Exposure to Infected Camels, Saudi Arabia, 2013 - Memish, Ziad A. (Centers for Disease Control and Prevention, 2014)
We investigated a case of human infection with Middle East respiratory syndrome coronavirus (MERS-CoV) after exposure to infected camels. Analysis of the whole human-derived virus and 15% of the camel-derived virus sequence yielded nucleotide polymorphism signatures suggestive of cross-species transmission. Camels may act as a direct source of human MERS-CoV infection.